Pelaksanaan Gadai Tanah Menurut Masyarakat Adat Madura - Khomaizah, Khomaizah; Tjoanda, Merry; Matuankotta, Jenny Kristiana (PATTIMURA Legal Journal, 2023)
Introduction: Agricultural land mortgage is the act of transferring land rights to another person which is done clearly and in cash, the party who transfer the title has the right to redeem the land. Than the transfer of land rights to the pawn is temporary. Facts in the field pawn land is done in a customary way, wich causes the mortgage time to last for years. This contradicts which law No. 5 of 1960 agrarian basic regulations and 7 paragraph 1 of law No. 56 of 1960 the determination of agricultural area. Purposes of the Research: This study aims to analyze the implementation of land pawning in the madurese indigenous people. Methods of the Research: The research approach method used is a statutory approach and a conceptual approach. The bahan hukum obtained in the form of primary bahan hukum and secondary bahan hukum and tertiary bahan hukum. This type of research is normative research through literature study. Bahan hukum were analyzed by qualitative analysis by presenting bahan hukum in narrative form. Results Originality of the Research: The results of the study show that the practice of pawning agricultural land in the madurese community continues for years, even to the customary heirs there. And do not follow according to the provisions 7 paragraph 1 of law No. 56 of 1960 the determination of agricultural area. This requires legal protection against the implementation of land pledges that are nt in accordance with artcle 7 of law No. 56 of 1960. The land mortgages that exceed 7 year must be returned to the owner without ransom. As well as legal consequences for the implementation of land pawning without a time limit that occurred in Waru Pamekasan Madura, that can be subject to a 3-mont sanction and or a maximum fine of 10.000.